Análise de fatores associados a melhora da amplitude de movimento em pacientes pediátricos com paralisia cerebral tratados com neurotoxina botulínica a - SILVA, Adriano Rodrigues da (2024)
This clinical cohort sought to demonstrate factors associated with a greater or lesser amplitude gain after the application of Botulinum Neurotoxin-A in paediatric patients at a reference hospital in Belém do Pará, as well as the joints most affected by the injection of the toxin. Goniometry was performed in 20 patients, including the ankle, knee and hip, before and after the application of the Toxin. The amplitudes in the two movements were compared with each other, as well as the influence of gender and age of the patients in question. It was identified that, with the exception of the knee, all joint movements analysed had a significantly greater range of motion compared to the pre-toxin. In addition, both gender and age of the patients did not influence the demonstrated result. In view of this, it is concluded that botulinum toxin has positive effects in improving the range of motion of most of the evaluated joints and can be used in the therapeutic arsenal together with physical rehabilitation measures to improve the quality of life and independence of patients affected by the cerebral palsy.